Comprehensive Assessment of Nitrogen Dioxide Concentration Dynamics in Konkan Region, India - A. Srivastava; A. K. Thakur; Pritipadmaja; R. D. Garg; P. K. Garg (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Air pollution is a primary environmental concern mainly in urban areas. Previous research on air pollution in the Konkan region has primarily focused on ground-based measurements, often lacking comprehensive spatial coverage and long-term trend analysis. This study uses satellite data of Sentinel-5P to examine the spatiotemporal trends and hazard zonation of NO2 concentrations in the Konkan region of Maharastra from 2019 to 2023. Various statistical tools such as central tendency and other parameter estimation, along with correspondence analysis were used to assess the variability. The classification was done using the binary mask having a threshold of 0.9*10−4, and logical operation was employed for hazard zonation. The classification reveals 2,065 sq. km. of the area under the highest hazard level. The analysis also highlighted that the mean NO2 concentration rose from 0.7027 × 10−4 mole/m2 in 2019 to 0.7680 × 10−4 mole/m2 in 2023, with consistent spatial variability. It may be attributed to persistent emission sources like industrial zones and highways. Spatial correspondence analysis revealed strong associations between consecutive years but a decline over longer periods. However, the overall association value was quite high over the study period. Persistent pollution is observed in areas like Thane, Mumbai, Navi Mumbai, Washi, Dadar and Colaba, along with the highest level of hazard. It reflects the consistency of pollution over a certain area and the need for targeted intervention for pollution control and sustainable environmental development. Overall, this study underscores the significance of satellite-based monitoring for identifying pollution trends and hotspots. It also offers insights into evidence-based mitigation strategies to improve air quality and protect public health.